2018
DOI: 10.15611/fins.2018.4.06
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the importance of the true and fair view (TFV) principle. The case of Poland

Abstract: The aim of this paper is to analyse matters of truth, which is inherent issue of accounting (and therefore in reporting, as its part), which is reflected in the true and fair principle (TFV). The paper demonstrates the essence of the TFV principle and the evolution of its role and place among the set of qualitative characteristics of financial statements. After examining the changes in the development of the perception of TFV the paper makes an appraisal, gives the author's comments and contribution by providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A financial statement must present data of adequate quality, compliant with the principles and guidelines contained in the accounting law and consistent with the accounting theory in order to properly perform its functions (information, control and analytical functions). The basis of the accounting concept underlying the quality of financial information is the true and fair view concept [3,4,5]. For many years, business practice has shown that certain company assets are of particular importance to its economic and sustainability image.…”
Section: Introductionmentioning
confidence: 99%
“…A financial statement must present data of adequate quality, compliant with the principles and guidelines contained in the accounting law and consistent with the accounting theory in order to properly perform its functions (information, control and analytical functions). The basis of the accounting concept underlying the quality of financial information is the true and fair view concept [3,4,5]. For many years, business practice has shown that certain company assets are of particular importance to its economic and sustainability image.…”
Section: Introductionmentioning
confidence: 99%